Help motivation: Preconditions for altruistic behaviour - Suslavičius, A. (Psichologija, 1991)
Social and biological treatments of help motivation, the decision-making dynamics of helping processes of personality due to situation conditions and to other factors are discussed. The key notions of the article are victim motive conflict, challenge to self-esteem. Mechanisms of receiving help and personality characteristics of help receiving are also being discussed.